Simulation analysis on patient visit efficiency of a typical VA primary care clinic with complex characteristics - Shi, Jing; Peng, Yidong; Erdem, Ergin (Simulation modelling practice and theory, 2014)
In this paper, we develop a simulation model to study the performance of clinic operations based on the settings of a typical VA primary care clinic with complex characteristics. The clinic serves three different types of patients, namely, regular appointment patients, walk-in patients, and nurse-only patients, and they each have different patient flow routes. The model captures the patient flow characteristics of the studied clinic, and it is validated by comparing the simulation results with the real key performance measures obtained from in the clinic. The system performance is mainly measured by two metrics: one is how the clinic makes efficient use of its resources, and the other is how long the patients need to wait for services. A scenario analysis is conducted which adopts the experiment design method for multiple factors to study the effect of six parameters on the system performance. The six parameters are walk-in arrival rate, no-show rate, post-triage rate, new patient rate, number of double booking, and nurse-only appointment rate. Based on the results, one major recommendation for the clinic is to reduce or eliminate the use of double booking because it causes the dramatic increase of patient waiting time. Also, based on the projection of the high new patient rate in the near future, it is recommended that the clinic manage the walk-in patient load by adjusting the existing admission policy. In addition, for the clinic with already high provider utilization, interventions for reducing patient no-show rate alone may further deteriorate the congestion of patient visit in the clinic.